Productivity and water use efficiency of bread wheat (Triticum aestivum L.) as influenced by irrigation schedule, mulching and hydrogel in eastern Indo-Gangetic plains of India - Singh, SP; Singh, RK; Prasad, SK; Bisen, Neelam (Bangladesh Journal of Botany, 2018)
A field experiment was conducted to evaluate the influence of limited and adequate irrigation and moisture conservation practices (rice straw mulch and hydrogel) on yield and water use efficiency in wheat. Though, maximum wheat yield (3.92 t/ha) and water use efficiency (15.72 kg/ha/mm) was recorded with four irrigations at crown root initiation stage, tillering, late jointing, and milk stage, two irrigations applied at tillering and flowering and soil mix drilling of 7.5 kg/ha hydrogel (a synthetic polymer) at sowing produced comparable yield (3.34 t/ha) with less water use, enhancing the water use efficiency (15.45 kg/ha-mm). The higher net return and B : C ratio were found in the treatment 2.5 kg/ha hydrogel. Thus, from present study it may be concluded that under limited irrigation conditions, water conservation practices like soil mix drilling of hydrogel and rice-straw mulching are beneficial for maintaining optimum moisture in soil to enhance wheat yield and water use efficiency.